2021
DOI: 10.1017/s0033291721001744
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of obsessive-compulsive disorder

Abstract: Background Obsessive-compulsive disorder (OCD) is a psychiatric disorder with multiple symptom dimensions (e.g. contamination, symmetry). OCD clusters in families and decades of twin studies clearly demonstrate an important role for genetics in the etiology of the disorder. Methods In this review, we summarize the genetic epidemiology and molecular genetic studies of OCD and obsessive-compulsive symptoms. Results OCD is a heritable, polygenic disorder with contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 158 publications
(201 reference statements)
3
29
0
5
Order By: Relevance
“…In pediatric OCD, individuals have a two-fold higher risk of having a first-degree relative with OCD as compared to adult-onset cases. The current understanding of the genetics of OCD has been extensively reviewed in the literature ( 23 ).…”
Section: Symptom Presentationmentioning
confidence: 99%
“…In pediatric OCD, individuals have a two-fold higher risk of having a first-degree relative with OCD as compared to adult-onset cases. The current understanding of the genetics of OCD has been extensively reviewed in the literature ( 23 ).…”
Section: Symptom Presentationmentioning
confidence: 99%
“…Although the etiology of OCD is unknown, a study on magnetic resonance spectroscopy has suggested dominance of excitatory versus inhibitory factors in brain circuits during goaldirected behaviors (Ivarsson et al, 2021). OCD clusters in families and twin studies have demonstrated that it is a heritable, polygenic disorder that shares genetic risk with comorbid anorexia nervosa and Tourette syndrome (Mahjani et al, 2021).…”
Section: Obsessive Compulsive Disordermentioning
confidence: 99%
“…Rare secondary forms of OCD may occur in the context of genetic syndromes, such as Turner syndrome (Moonga et al 2017 ). To date, little is known about syndromic OCD (Mahjani et al 2021 ). The rationale of the current paper is to describe the first patient with obsessive–compulsive symptoms (OCS) and ACTG1 -associated Baraitser-Winter cerebrofrontofacial syndrome.…”
Section: Introductionmentioning
confidence: 99%